Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2019 - Casas-Sánchez, José Miguel (2019)
A stratified random bottom trawl survey on Flemish Cap was carried out from June 29th to July 29th 2019. The area surveyed was extended up to depths of 800 fathoms (1450 meters) following the same procedures as in previous years. This year a total of 180 valid hauls were made by the vessel R/V Vizconde de Eza with the usual survey gear (Lofoten), 120 up to 730 meters depth. The surveyed area has properly prospected the 32 strata planned. The general indexes for shrimp were estimated taken into account the traditional swept area (strata 1-19, up to depths of 730 m.) and the total area surveyed (strata 1-34, up to depths of 1450 m.). As the last years the strata 26 and 27sited in the southeast of the bank with depths from 600 to 800 fathoms (1100- 1400 m.) will not be surveyed due to the presence in the bottoms of great quantities of mud and sponges. The results concerning shrimp are presented and compared to those from previous years of the same series. The total biomass indexes have increased significantly since 2015 and they are now well above Blim. The total and female biomasses estimated in 2019 were 9273 t and 8486 t respectively. As in previous years the youngest specimens (age 1, around 10 mm CL) barely appeared in the catches and the abundance at age 2 (around 16 mm CL) was similar to the estimated in 2018 at levels next to reported in 2009 and 2010. However unlike 2018 the abundance at age 2 in the small mesh size bag attached on the cod-end showed a significantly increasing that it could confirm the upward trend in the recent recruitments initiated from 2014. Also in 2019 the estimated abundance at age 1 in the juvenile bag was the second highest value in the historical series. If this strong year-class (2018) was confirmed in 2020 it would improve the state of impaired recruitment and contribute to the recovery of stock. The stock after five years of continuous increases of biomass, now it has very low probability of being bellow Blim, allowing a small amount of direct fishing on this stock. ...